An acid-tolerance response system protecting exponentially growing Escherichia coli - Ying Xu (Nature Portfolio, 2020)
The ability to grow at acidic pH is crucial for E. coli colonization of the host’s intestine. Here, the authors identify an acid-tolerance response system that is important for E. coli exponential growth at pH 4.2, survival in the mouse intestine, and production of 3-hydroxypropionate during fermentation.